Development of a reverse transcription loop-mediated isothermal amplification assay for the rapid diagnosis of avian influenza A (H7N9) virus infection - Nakauchi, Mina; Takayama, Ikuyo; Takahashi, Hitoshi; Tashiro, Masato; Kageyama, Tsutomu (Journal of virological methods, 2014)
•The reverse transcription-loop-mediated isothermal amplification assay was developed to detect avian influenza A (H7N9) virus epidemic in China.•The developed assays were evaluated using in vitro transcribed control RNA, clinical specimens, and clinical isolates.•The assays were shown to have high sensitivity and high specificity. A genetic diagnosis system for detecting avian influenza A (H7N9) virus infection using reverse transcription-loop-mediated isothermal amplification (RT-LAMP) technology was developed. The RT-LAMP assay showed no cross-reactivity with seasonal influenza A (H3N2 and H1N1pdm09) or influenza B viruses circulating in humans or with avian influenza A (H5N1) viruses. The sensitivity of the RT-LAMP assay was 42.47copies/reaction. Considering the high specificity and sensitivity of the assay for detecting the avian influenza A (H7N9) virus and that the reaction was completed within 30min, the RT-LAMP assay developed in this study is a promising rapid diagnostic tool for avian influenza A (H7N9) virus infection.